2019
DOI: 10.1039/c8ra09297d
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption capacity of kelp-like electrospun nanofibers immobilized with bayberry tannin for uranium(vi) extraction from seawater

Abstract: A novel kelp-like gelatin/PVA composite nanofiber band loaded with bayberry tannin was fabricated for the extraction of uranium(vi) from seawater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…With increasing solution pH when U is mainly present as negatively charged species (UO 2 ) 3 (OH) 7 - and (UO 2 )(OH) 3 - , the removal efficiency increased due to the electrostatic attraction between the negatively charged U(VI) species and the positively charged sorbent 56 . When the pH further increased, the hydrolysation of UO 2 2+ and formation of U(VI)-carbonate species (UO 2 ) 2 (CO 3 )(OH) 3− inhibited the U(VI) adsorption, which decreased the adsorption capacity 57 . Therefore, an optimal pH of 3.0 was used in subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…With increasing solution pH when U is mainly present as negatively charged species (UO 2 ) 3 (OH) 7 - and (UO 2 )(OH) 3 - , the removal efficiency increased due to the electrostatic attraction between the negatively charged U(VI) species and the positively charged sorbent 56 . When the pH further increased, the hydrolysation of UO 2 2+ and formation of U(VI)-carbonate species (UO 2 ) 2 (CO 3 )(OH) 3− inhibited the U(VI) adsorption, which decreased the adsorption capacity 57 . Therefore, an optimal pH of 3.0 was used in subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The neutral dyes of MB and RhB were adsorbed because of the π–π stacking and the hydrogen‐bonding interactions between dye molecules and hydrogel species. [ 45 ] The least yield of adsorption was observed for the negatively charged dye, RBg, owing to its repulsive electrostatic interaction with negatively charged graphene surface, [ 46 ] which is yet in competition with resulted in π–π stacking and the hydrogen bonding interactions. The UV spectra in Figure 9 in line with observations of adsorption experiment cuvettes in Figure , clearly revealed that the order of adsorption affinity is as follows: positively charged > neutral > negatively charged dyes as there are different interactions between each dye and rGOSH.…”
Section: Resultsmentioning
confidence: 99%
“…Many types of sustainable materials have been fabricated by electrospinning, including adsorption [96] and filter materials [71] used in environmental management, bioengineering materials with biological affinity [28], and drug delivery vehicles that regulate the rate of drug release [97]. For example, as a manufacturing technique for biomedical materials, Meng et al [98] electrospun gelatin/polyvinyl alcohol-based materials, and Cheng et al [28] electrospun a biodegradable cellulose nanocrystal membrane. Both of them overcome the limitation of cell adhesion and migration by adjusting the hydrophobicity of the nanofiber membrane.…”
Section: Application Of Electrospun Sustainable Composite Materialsmentioning
confidence: 99%